Association of childhood socioeconomic status with adulthood maximal exercise blood pressure : the Cardiovascular Risk in Young Finns Study - Kähönen, Erika (Taylor & Francis, 2025)
Socioeconomic status has been related to resting blood pressure (BP) levels at different stages of life. However, the association of childhood socioeconomic status (SES) and adulthood exercise BP is largely unknown. Therefore, we studied the association of childhood SES with adulthood maximal exercise BP. This investigation consisted of 373 individuals (53\% women) participating in the Cardiovascular Risk in Young Finns Study who had data concerning family SES in childhood (baseline in 1980, at age of 6–18 years) and exercise BP response data in adulthood (follow-up in adulthood in 27–29 years since baseline). A maximal cardiopulmonary exercise test with BP measurements was performed by participants, and peak exercise BP was measured. In stepwise multivariable analysis including childhood risk factors and lifestyle factors (body mass index, systolic BP, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglycerides, insulin, fruit consumption, vegetable consumption, and physical activity), lower family SES in childhood was associated with higher maximal exercise BP in adulthood (β value ± SE, 1.63 ± 0.77, p = 0.035). The association remained significant after further adjustment with participants SES in adulthood (β value ± SE, 1.68 ± 0.65, p = 0.011) and after further adjustment with adulthood body-mass index, systolic BP, maximal exercise capacity, and peak heart rate in exercise (β value ± SE, 1.25 ± 0.56, p = 0.027). These findings suggest that lower childhood family SES is associated with higher maximal exercise BP in adulthood. Limited data are available about the association of childhood socioeconomic status and adulthood exercise blood pressure. We prospectively examined whether childhood socioeconomic status is associated with adulthood exercise blood pressure in 373 participants aged 6–18 years at baseline (1980) from the longitudinal Cardiovascular Risk in Young Finns cohort study. In multivariable analysis, including childhood cardiovascular risk factors and lifestyle factors, lower family socioeconomic status in childhood was associated with higher maximal exercise blood pressure in adulthood. The association remained significant after further adjustment with participants socioeconomic status in adulthood and also after further adjustment with adulthood body mass index, systolic blood pressure, maximal exercise capacity and peak heart rate in exercise. Low childhood socioeconomic status predicted also higher risk of exaggerated exercise blood pressure response in adulthood, although this finding was diluted to non-significant after adjustment with adulthood body mass index and systolic blood pressure. These findings suggest that lower childhood family socioeconomic status is associated with higher maximal exercise blood pressure in adulthood.